A Quantification of Virtual Water Trade in Relation to Agricultural Products of Iran - Boshrabadi, Hossein Mehrabi (Asian Journal of Agriculture and Development, 2010)
The seriousness of the water crisis has increased in recent years in Iran which has an arid and semi-arid climate. Nowadays, "virtual water" is fast emerging to be an important concept in water resource management. Virtual water is defined as the volume of water required to produce a commodity or service (e.g., vegetable products, fish and seafood, animal products). When commodities enter the international market, virtual market trade takes place. Water-use planning and agricultural trade pattern are thus two components that are developing to be of great importance to food security in Iran. This paper presents an analysis of virtual water trade in Iran. It introduces a method for quantification and evaluation of water hidden in export and import agriculture products from 1996-2006 in Iran. For each product, virtual water content was calculated. Results indicate that the trend of virtual water import is decreasing. Based on crop trade, Iran has more virtual water imports that the trend exports. However, virtual water export increased from 1996 until 2006. Because of the high opportunity cost of water in arid and semi-arid countries like Iran, it is recommended that environmental effects of virtual water trade should be further studied.